The Gompertz flexible Weibull distribution and its applications - Khaleel, Munddher Abdullah; Oguntunde, Pelumi E.; Ahmed, M. T.; Ibrahim, Noor Akma; Loh, Yue Fang (Institute for Mathematical Research, Universiti Putra Malaysia, 2020)
This paper introduces the Gompertz flexible Weibull distribution as an extension of the flexible Weibull distribution. Its various statistical properties are obtained and established while the method of maximum likelihood estimation is used in estimating the unknown model parameters. The application of Gompertz flexible Weibull distribution is illustrated by making use of three real life data sets, this is done to demonstrate its potentials over some other important distributions like the Gompertz Weibull, Gompertz Burr type XII, Gompertz Lomax, exponentiated flexible Weibull, exponentiated flexible Weibull extension and Kumaraswamy flexible Weibull distributions. Simulation studies were also conducted and the behavior of the Gompertz flexible Weibull parameters were investigated.